Penyimpanan Serbuk Sari Jagung dan Potensinya untuk Produksi Benih Hibrida - Fariroh, Indri; Palupi, Endah Retno; Suwarno, dan Faiza Chairani (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Production of maize hybrid seed is hindered by relatively poor production by the male line pollen; short live of the pollen which was ascribed to desiccation and dehydration sensitive and flowering asynchrony between male and female lines. The aims of this study were to enhance production and viability of male line pollen and also to determine the suitable storage condition for maintaining pollen viability in order to be used for production of hybrid seed. The research consisted of two experiments. The first experiment was arranged in split plot randomized block design with NPK dosages as main plot (0, 300, 600, 900 kg ha-1) and application of boron as sub-plot (0, 1.5, 3, 4.5, 6 kg ha-1), replicated three times. The second experiment used randomized block design with two factors, i.e. storage temperature (-196 oC and -20 oC) and storage period (0, 1, 2, 3, 4 weeks). The result showed that NPK 900 kg ha-1 increased the number of spike per tassel from 9.3 to 10.7. Application of NPK 600 kg ha-1 or boron 1.5 kg ha-1 improved pollen viability. Combination of NPK 900 kg ha-1 and boron 6 kg ha-1 resulted in the highest pollen viability of 95.3%. Pollen after being stored for four weeks either in -196 ºC or -20 ºC was possible to be used for seed production with 20% seed set.Keywords: boron, freezer, liquid nitrogen, NPK dosage, pollen viability